Efficient high-pass filtering with practical, high-yield X-ray transmission mirror optics. (December 2020) - Agyeman-Budu, David N.; Brock, Joel D.; Woll, Arthur R.
Abstract : Although the concept, first demonstration, and potential applications of X-ray transmission mirrors (XTMs) were initially described over 30 years ago, only a few implementations exist in the literature. This is attributed to the unsolved challenge of a thick frame supporting a thin, reflecting membrane which does not itself block the transmitted beam. Here, we introduce a novel approach to solve this problem by employing silicon microfabrication. A robust XTM frame has been fabricated by using a novel two-step etch process, which secures the thin-film membrane without blocking the transmitted beam. Specifically, we have fabricated delicate XTM optics with 90% yield, which consist of 280-nm-thick low-stress silicon nitride membrane windows that are 1.5 mm wide and 125 mm long on silicon substrates. The XTM optics have been demonstrated to be a more efficient high-pass X-ray filter; for example, when configured for 40% transmission of 11.3 keV photons, we measure the reduction of 8.4 keV photons by a factor of 56.